A logistic regression approach to compare the priority banking in CIMB preferred: A case study in Kuala Lumpur, Malaysia / Siti Nur Amirah Ab Aziz - Ab Aziz, Siti Nur Amirah (Bachelor of Science (Hons.) Statistics, 2015)
CIMB Preferred is a regional priority banking service offered in Malaysia, Singapore, Thailand, Indonesia and Cambodia. The banking service targets the upper level of customer to liaise with. A comparison between Prime Banking and Preferred Banking is being evaluated. Both type of banking were operated by CIMB Preferred. A secondary data involving 126 relationship managers from Prime Banking and 376 relationship managers from Preferred Banking was included in the study. A Chi-square test of association and logistic regression analyses had been conducted. The descriptive analyses recorded Chinese was the majority race among all relationship managers in both Prime and Preferred Banking. While south Malaysia recorded the highest number of branch with relationship managers. Chi-square test of association was conducted to analyses the association between staff race and branches location. Both banking discovered no significant association between staff race and branches location. The Prime and Preferred Banking were being compared using logistic regression approach. Two model of logistic regression for each type of banking had been developed. The study recorded Preferred Banking model had two significant variables. They were variables new (odd ratio=1.003, p=0.016) and in progress (odd ratio=0.928, p=0.032). The study had found most of activities in CIMB Preferred were contributed by relationship managers in Prime Banking